2013
DOI: 10.18357/ijcyfs41201311852
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Diversity and Youth Offending: An Examination of Risk and Protective Factors

Abstract: This study examined risk and protective factors for criminal reoffending behaviour among a group of Canadian young people who had committed at least one substantive criminal offence in the past and fell into one of four ethnic groups: (a) Canadian born, parents Canadian born; (b) Aboriginal/Métis; (c) first or second generation immigrant, Caucasian; and (d) first or second generation immigrant, other ethnic background. Risk and protective factors were classified into five domains: individual; family; peer; sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, they found that Canadian Aboriginal offending youth were more likely than non-Aboriginal youth to offend against girls below 12 years old who were known to them (peers or family), and had higher recidivism rates (specifically violent, sexual, and non-sexual reoffending) in their 10-year follow-up. Some of these findings were replicated by Bertrand, MacRae-Krisa, Costello, and Winterdyk (2013), whose examination of risk and protective factors in Canadian offending youth (including those who sexually harmed) identified significant differences between Aboriginal and non-Aboriginal Canadians. In that study, Aboriginal youth were more likely to also have experienced foster care, criminal involvement by family members, familial substance abuse, and gangs present within their community.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, they found that Canadian Aboriginal offending youth were more likely than non-Aboriginal youth to offend against girls below 12 years old who were known to them (peers or family), and had higher recidivism rates (specifically violent, sexual, and non-sexual reoffending) in their 10-year follow-up. Some of these findings were replicated by Bertrand, MacRae-Krisa, Costello, and Winterdyk (2013), whose examination of risk and protective factors in Canadian offending youth (including those who sexually harmed) identified significant differences between Aboriginal and non-Aboriginal Canadians. In that study, Aboriginal youth were more likely to also have experienced foster care, criminal involvement by family members, familial substance abuse, and gangs present within their community.…”
Section: Introductionmentioning
confidence: 89%
“…Developmental risk factors were identified as those being present in the youth’s history prior to their onset sexual offense. Characteristics were prespecified, selected from known criminological factors associated with violent and antisocial youth (Andrews & Bonta, 2010; Loeber & Farrington, 1999) as well as previously identified characteristics of Indigenous youth who have sexually harmed (Bertrand et al, 2013; Rojas & Gretton, 2007). The impact of these experiences, attitudes, and behaviors on each participant’s individual, social, and academic functioning was considered in determining presence for each risk factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation